Autonomous low-cost network of ozone sensors: to study the spatial distribution and exposure in underserved agricultural communities in central California - Gunniah Vijayakumar, Akshay Kumar, author; Jathar, Shantanu, advisor; L'Orange, Christian, committee member; Magzamen, Sheryl, committee member; Quinn, Casey, committee member; Carter, Ellison, committee member (Colorado State University. Libraries, 2025)
Ozone (O3), a criteria air pollutant, is often overlooked in rural and remote regions, leaving the spatial distribution and exposure levels poorly understood, particularly in underserved communities. In this study, we developed and deployed a network of 12 autonomous, low-cost, and solar-powered air quality monitoring units (VOZboxes) in California's San Joaquin Valley (SJV). Co-located with a reference monitor in Fresno, CA, the VOZboxes underwent calibration before and after field deployment in June and November 2023, respectively, to measure O3 concentrations over a dynamic range of 20 to 100 ppbv with an RMSE < 5 ppbv. Deployed across 11 unique locations in SJV from July to November 2023 at varying periods, the VOZboxes revealed modest spatial variability in O3 mixing ratios, with elevated concentrations recorded in bigger cities and smaller eastern townships, while lower concentrations were found in smaller western regions. By leveraging multivariate regression models for data calibration, the VOZboxes effectively assessed compliance with the national ambient air quality standard (NAAQS) for O3 (maximum daily 8-hour average of 70 ppbv) across locations. This study underscores the potential of low-cost environmental sensors for characterizing air quality and O3 exposure in rural and remote environments. Additionally, it emphasizes their utility as tools for addressing the monitoring needs of underserved communities and acts as a tool for environmental justice.
Keywords: low cost sensors; VOZbox; ozone sensors; compliance